Процесуалізація права у Франції та Німеччині в епоху Середньовіччя - Слинько, Д. В.; Slynko, D. V.; Дмитро Слинько (Юридичний науковий електронний журнал. - 2018. - № 2. - С. 28-31, 2018)
Стаття присвячена висвітленню однієї з актуальних історико-правових проблем щодо процесуалізації права у країнах середньовічної Європи, зокрема Франції та Німеччини. Норми права цих країн, у тому числі процесуальні, у майбутньому стали підґрунтям формування романо-германської правової системи. Спочатку основною формою втілення процесуальних норм виступає обвинувально-змагальний процес, який отримав свою регламентацію ще у варварських правдах та характеризувався однаковістю процедури у кримінальних та цивільних справах. Згодом у церковних судах все більшого розповсюдження набуває розшуково-інквізиційний процес, що базувався на формальній теорії доказів. Внаслідок ускладнення суспільного життя та зміцнення державної королівської влади він починає витісняти обвинувально-змагальний процес.

The article is devoted to the coverage of one of the most relevant historical and legal problems concerning the process of law-making in the medieval European countries, in particular France and Germany. The procedural law of these countries in the future became the basis for the formation ofthe Romano-Germanic legal system. It was established that initially the main form ofthe implementation of procedural norms is the prosecution-contest process, which received its regulation in barbaric truths and was characterized by the uniformity ofthe procedure in criminal and civil cases. Subsequently, in the church courts, the search-inquisition process, which was based on the formal theory of evidence, is becoming more widespread. The final prosecution-process was abolished by the ordinance of 1498 and the edict of1539. The leading idea of the investigative-inquisitorial process was the presumption of guilt, so a suspect (accused) could have been subjected to torture based on testimony of a person who was considered a witness. The purpose of the process was considered to have been achieved if the accused person was recognized. The materials ofthe investigation conducted played a decisive role during the trial ofthe case. There was a certain gap between the previous one and the trial. The defendant did not have a real opportunity to defend himself, despite having read the materials of the investigation. In the case of both acquittal and indictment, the court took into account, as a rule, evidence of a prosecution. The judge had the right to reappoint the defendant’s torture if he doubted their credibility. After the announcement ofthe sentence in order to establish unknown accomplices, the so-called final torture could be applied. The inquisition process had the following characteristics: the presentation of a prosecution on behalf of the state by a judge as an official; investigative actions are public-legal, not private-nature; application to suspected methods of physical influence; conducting of a court session, as a rule, in the closed mode; written design. The prosecution process for Carolina was divided into the following stages: inquiry, general investigation, special investigation, sentencing. As a result of the complication of public life and the strengthening of state royal power, he begins to oust the prosecution-contest process.

Статья посвящена рассмотрению одной из актуальных историко-правовых проблем - процессуализации права в странах средневековой Европы, в частности Франции и Германии. Нормы права этих стран, в том числе процессуальные, в будущем стали основой формирования романо-германской правовой системы. Сначала основной формой воплощения процессуальных норм выступает обвинительно-соревновательный процесс, который получил свою регламентацию еще в варварских правдах и характеризовался единообразием процедуры по уголовным и гражданским делам. Впоследствии в церковных судах все большее распространение приобретает розыскной инквизиционный процесс, основанный на формальной теории доказательств. Вследствие развития общественной жизни и укрепления государственной королевской власти он начинает вытеснять обвинительно-соревновательный процесс.
Keywords: Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; Історія. History. История; історія держави і права; середньовічна історія; Середньовіччя; Средневековье; Middle Ages; Франція; Німеччина; Франция; Германия; France; Germany; процесуальні норми; обвинувально-змагальний процес; розшуково-інквізиційний процес; стадії судового процесу; попереднє розслідування; процессуальные нормы; обвинительно-соревновательный процесс; розыскной инквизиционный процесс; стадии судебного процесса; предварительное расследование; procedural norms; prosecution-contest process; search-inquisition process; stages of judicial process; preliminary investigation